2019
DOI: 10.1080/13803395.2019.1621268
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Structured Interview of Reported Symptoms (SIRS-2) in detecting feigned adult attention-deficit/hyperactivity disorder

Abstract: Introduction: The Structured Interview of Reported Symptoms (SIRS-2) utilizes various strategies in the detection of simulated psychiatric disorders. The present study aimed to examine which of these strategies proves most useful in uncovering feigned attention deficit hyperactivity disorder (ADHD) in adulthood. Method: One-hundred seventy-one individuals instructed to feign ADHD were compared to 46 genuine patients with ADHD as well as 99 neurotypical controls in their reports provided on the SIRS-2. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Adaptation of detection strategies previously described by Rogers (2018) may be useful additions or alternatives to the reliance on erroneous stereotypes, according to the authors. They suggest that inquiries into symptom combinations, which are rarely reported jointly by genuine patients, may present another basis on which to formulate ADHD-specific items for validity tests; a recommendation supported by findings published recently (Becke et al 2019).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Adaptation of detection strategies previously described by Rogers (2018) may be useful additions or alternatives to the reliance on erroneous stereotypes, according to the authors. They suggest that inquiries into symptom combinations, which are rarely reported jointly by genuine patients, may present another basis on which to formulate ADHD-specific items for validity tests; a recommendation supported by findings published recently (Becke et al 2019).…”
Section: Introductionmentioning
confidence: 87%
“…Diagnoses of ADHD were secured through a comprehensive clinical work-up and confirmed by at least two experienced clinicians. The diagnostic process included a psychiatric interview, which enquired both past and present symptoms of ADHD in accordance with the DSM criteria (American Psychiatric Association 2013; Barkley and Murphy 1998). Additionally, participants scored above the recommended cut-offs on two standardized self-report rating scales, which tapped symptoms of ADHD across the same time span (WURS-K and ASR) (Adler et al 2006;Kessler et al 2005a, b;Ward et al 1993).…”
Section: Participantsmentioning
confidence: 99%
“…While the CII, EI, and Ds-ADHD utilize items drawn from existing instruments, the INF and the ACI each contain disorder-specific items written specifically for the purpose of detecting noncredible self-report in the clinical assessment of ADHD. The ACI's items were developed as ADHD-specific adaptations of detection strategies described by Rogers (Becke et al, 2019;Rogers, 2018). Initial validation studies showed comparable classification accuracy for the Ds-ADHD and INF, whereas the performance of the ACI was comparable to the CII's classification accuracy.…”
mentioning
confidence: 99%